2021
DOI: 10.3389/fonc.2021.731441
|View full text |Cite
|
Sign up to set email alerts
|

Potential Molecular Biomarkers of Vestibular Schwannoma Growth: Progress and Prospects

Abstract: Vestibular schwannomas (VSs, also known as acoustic neuromas) are relatively rare benign brain tumors stem from the Schwann cells of the eighth cranial nerve. Tumor growth is the paramount factor for neurosurgeons to decide whether to choose aggressive treatment approach or careful follow-up with regular magnetic resonance imaging (MRI), as surgery and radiation can introduce significant trauma and affect neurological function, while tumor enlargement during long-term follow-up will compress the adjacent nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 171 publications
(249 reference statements)
2
17
0
Order By: Relevance
“…Among ether lysophospholipids, the primary member is the Platelet Activating Factor (PAF) [ 37 ], a potent effector of inflammation produced by basophils, which could be recruited at the tumor site. The enhanced level of ether lysophospholipids in schwannomas agreed with an inflammatory hallmark present in these tumors, as previously reported for vestibular schwannomas [ 38 , 39 ]. Pro-inflammatory cytokines, including TGF-β1, TNF-α, IL-1β, and IL-6, may be secreted by activated leukocytes, fibroblasts, and Schwann cells [ 39 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Among ether lysophospholipids, the primary member is the Platelet Activating Factor (PAF) [ 37 ], a potent effector of inflammation produced by basophils, which could be recruited at the tumor site. The enhanced level of ether lysophospholipids in schwannomas agreed with an inflammatory hallmark present in these tumors, as previously reported for vestibular schwannomas [ 38 , 39 ]. Pro-inflammatory cytokines, including TGF-β1, TNF-α, IL-1β, and IL-6, may be secreted by activated leukocytes, fibroblasts, and Schwann cells [ 39 ].…”
Section: Discussionsupporting
confidence: 88%
“…Neurosurgical procedures were carried out under general anesthesia and microscopic view. According to our institutional protocol for peripheral nerve surgery and the literature recommendations [ 9 , 10 , 38 ], intraoperative neurophysiological monitoring was performed when indicated to identify functioning fascicles and localize the safest entry point inside the tumor capsule. Immediately after excision, all tumor samples for lipidomic were cryopreserved and stored in liquid nitrogen at the Neurobiology laboratory according to standard operating procedures [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…The intensity of the NF-kB signaling pathway of intermediate monocytes was significantly higher than that of other clusters. Previous studies have shown that activated NF-κB is the mechanism responsible for the upregulated expression of p75NTR to promote the survival of Schwann cells ( Zhang et al, 2021 ). High NF-κB activity enhances hepatocyte growth factor (HGF) and the c-Met autocrine feedforward loop to promote tumor cell proliferation and increases the expression of prognostic factors in VS, such as matrix metalloproteinase 2 (MMP-2), MMP-9, MMP-14, COX-2, interleukin 1 (IL-1), IL-6, TNF- α ( Xu et al, 2019 ), and signal transduction transcriptional activator 1 (STAT1) ( Solinas et al, 2009 ), or the absolute tumor growth rate of VS ( Behling et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that through the analysis of Schwann cell transcription factors, we found that Schwann cells may promote the proliferation of vestibular schwannoma by promoting vascular proliferation through transcription factor PKNOX1. It has been reported that the expression of VEGF, VEGFR-1/Flt, VEGFR-2/Flk, and coreceptor NP1 in VS tissue is significantly higher than that in normal vestibular nerve, suggesting that at least part of tumor growth is achieved by promoting angiogenesis ( Zhang et al, 2021 ). This is consistent with our research results.…”
Section: Discussionmentioning
confidence: 99%
“…ErbB receptors were activated in both sporadic and NF2-related VSs, and EGFR expression levels correlated with Sch size [ 26 ]. Furthermore, EGF was upregulated in NF2-related VS but not in sporadic VS, suggesting that an EGFR inhibitor might have efficacy in NF2 patients [ 27 , 28 ].…”
Section: Protein-kinase-related Pathwaymentioning
confidence: 99%